2013
DOI: 10.1111/bju.12003
|View full text |Cite
|
Sign up to set email alerts
|

A 9‐year experience of renal injury at an Australian level 1 trauma centre

Abstract: Objective• To detail the 9-year experience of renal trauma at a modern Level 1 trauma centre and report on patterns of injury, management and complications. Patients and methods• We analysed 338 patients with renal injuries who presented to our institution over a 9-year period.• Data on demographics, clinical presentation, management and complications were recorded. Results• Males comprised 74.9% of patients with renal injuries and the highest incidence was amongst those aged 20-24 years.• Blunt injuries compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
53
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 13 publications
7
53
0
3
Order By: Relevance
“…Lanchon et al (16) reported the success rate of conservative treatment in patients with grade 4 and 5 renal traumas as 88% and 50%, respectively. In a study by Shoobridge et al (19), all patients with grade 1-2 injury, 94% of the patients with grade 3 injury, 90% of the patients with grade 4 injury, and 35% of the patients with grade 5 injury were followed conservatively. In a retrospective study by Ekşi et al conducted with 135 renal trauma cases, 86% of the patients were followed with conservative treatment, and exploration was performed for 18 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lanchon et al (16) reported the success rate of conservative treatment in patients with grade 4 and 5 renal traumas as 88% and 50%, respectively. In a study by Shoobridge et al (19), all patients with grade 1-2 injury, 94% of the patients with grade 3 injury, 90% of the patients with grade 4 injury, and 35% of the patients with grade 5 injury were followed conservatively. In a retrospective study by Ekşi et al conducted with 135 renal trauma cases, 86% of the patients were followed with conservative treatment, and exploration was performed for 18 patients.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] There has been a paradigm shift towards conservative management for severe blunt trauma. [1,[4][5][6][7][8][9] Successful management of renal injury depends upon accurate assessment of their extent. With the advancement in radiologic imaging modalities and the ready availability of computed tomography allows surgeon to be much more informed about the injuries that they are treating.…”
Section: Introductionmentioning
confidence: 99%
“…Вместе с тем в ретроспективном исследовании из Южно-Африканской Республики [65] представлены 174 пострадавших, в том числе огнестрельное ранение было у 87 (50%), колото-ре-заное -у 43 (25%), закрытая травма -у 44 (25%). Распределение механизмов травмы различается у городского и сельского населения, однако дорож-но-транспортные происшествия устойчиво зани-мают первое место среди причин закрытой травмы с примерной частотой 70% [91,101]. Падение с вы-соты находится на втором месте -около 30% [23,36].…”
unclassified
“…КT с КУ у гемодинамически стабильных паци-ентов является «золотым стандартом» диагностики травмы почек [53,76,83,89,91,99]. При правиль-ном выполнении она позволяет диагностировать все повреждения сосудов, паренхимы и собирательной системы почек, а также лоханочно-мочеточниково-го сегмента [19].…”
unclassified
See 1 more Smart Citation